2021
DOI: 10.1016/j.ptsp.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of resistance training principles in exercise interventions for lower limb tendinopathy: A systematic review

Abstract: Please cite as: Burton, I. (2020). The implementation of resistance training principles in exercise interventions for lower limb tendinopathy: A systematic review. SportRxiv

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 111 publications
0
37
0
Order By: Relevance
“…Given the increased research interest and clinical use of BFRT in musculoskeletal rehabilitation for non-tendon pathologies, the dearth of available studies applying BFRT to tendon pathologies could be considered somewhat surprising. This is particularly relevant considering resistance training is considered the gold-standard first-line treatment intervention for tendinopathies, particularly Achilles and patellar tendinopathy, due to a plethora of evidence showing the clinical efficacy of resistance training such as eccentric and heavy slow resistance training (Burton and McCormack, 2021 ). Perhaps the belief that resistance training in tendinopathy must include high training loads has been a limiting factor in the application of LL-BFRT and could explain why it is an underutilized tool in tendon rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased research interest and clinical use of BFRT in musculoskeletal rehabilitation for non-tendon pathologies, the dearth of available studies applying BFRT to tendon pathologies could be considered somewhat surprising. This is particularly relevant considering resistance training is considered the gold-standard first-line treatment intervention for tendinopathies, particularly Achilles and patellar tendinopathy, due to a plethora of evidence showing the clinical efficacy of resistance training such as eccentric and heavy slow resistance training (Burton and McCormack, 2021 ). Perhaps the belief that resistance training in tendinopathy must include high training loads has been a limiting factor in the application of LL-BFRT and could explain why it is an underutilized tool in tendon rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Many AT exercise programs favor bodyweight loading and increase resistance as tolerated (e.g., 5 kg increments in a backpack) [ 40 ]…”
Section: Figurementioning
confidence: 99%
“…Most studies use 12-week long exercise interventions, though positive results have been found at six weeks [ 40 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the possibility of developing a tendinopathy seems to be increased by the interaction between intrinsic (age, body structure, nutrition, metabolic, genetic) and extrinsic factors (fatigue, improper loading, disuse, exogenous damage) [9,10]. Among them, tendon overload in sports or in specific work activities has been reported to be a crucial factor promoting 2 of 14 tendinopathies [11,12]. Similarly, some metabolic and hormonal imbalances, including diabetes, thyroid hormones, estrogens, testosterone, growth hormone, cortisol, cholesterol and glutamatergic changes, occur [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%